Impact of Poverty and Religion on Sexual Coercion experienced by University Female Students - Olusegun, Grace Funmilayo (Advances in Social Sciences Research Journal, 2020)
The study investigated the impact of religion and poverty on sexual coercion experienced among University female students in Nigeria Universities. The descriptive design of the survey type was employed for the study. The sample consisted of 1,200 sexually coerced female students, selected from nine universities drawn from South West using purposive sampling technique, simple random and stratified random sampling techniques. An instrument titled ‘Sexual Coercion Questionnaire’ was used. Test re-test method was used to establish the reliability of the instrument. The reliability coefficient of 0.75 was obtained. Analysis of Variance and t-test were used to test the hypotheses generated at 0.05 level of significance. It was revealed that sexual coercion experienced by female university students will depend on the type of religion practiced. It was also found that perpetrators will sexually coerce female students irrespective of their financial status. It was therefore recommended that the intensity of religious activities must be increased in Nigerian universities. More so, Professional Counselors should team up with the University administrators to fight sexual coercive behaviours among University Students and that anyone found guilty of sexual coercion should be punished.